2018
DOI: 10.1177/0956797618785899
|View full text |Cite
|
Sign up to set email alerts
|

Speech Is Silver, Nonverbal Behavior Is Gold: How Implicit Partner Evaluations Affect Dyadic Interactions in Close Relationships

Abstract: Growing evidence suggests that the seeds of relationship decay can be detected via implicit partner evaluations even when explicit evaluations fail to do so. However, little is known about the concrete daily relational processes that explain why these gut feelings are such important determinants of relationships’ long-term outcomes. The present integrative multimethod research yielded a novel finding: that participants with more positive implicit partner evaluations exhibited more constructive nonverbal (but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 39 publications
(54 reference statements)
2
42
1
Order By: Relevance
“…The present findings challenge the common assumption that implicit associations, and implicit bias more generally, have poor predictive validity (Jost, 2018). On the contrary, these findings add to recent research, showing that indirect measures of implicit cognition predict real-world behavior better than explicit measures (Faure et al, 2018;Kurdi et al, 2018;Nock & Banaji, 2007;Roland et al, 2018;Serra et al, 2019). The present findings also have clear clinical implications.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The present findings challenge the common assumption that implicit associations, and implicit bias more generally, have poor predictive validity (Jost, 2018). On the contrary, these findings add to recent research, showing that indirect measures of implicit cognition predict real-world behavior better than explicit measures (Faure et al, 2018;Kurdi et al, 2018;Nock & Banaji, 2007;Roland et al, 2018;Serra et al, 2019). The present findings also have clear clinical implications.…”
Section: Discussionsupporting
confidence: 74%
“…From a theoretical viewpoint, Nock et al's (2010) findings are important, because they contributed to a growing body of work showing that the implicit association test (IAT) has good predictive validity (Faure, Righetti, Seibel, & Hofmann, 2018;Glenn, Werntz et al, 2017;Greenwald, Poehlman, Uhlmann, & Banaji, 2009;Kurdi et al, 2018;Nock & Banaji, 2007;Roland, Mierop, Frenay, & Corneille, 2018;Serra et al, 2019). The question of whether the IAT can predict complex behavior over and above existing measures has generated considerable debate and controversy in social psychology (for a recent review, see Jost, 2018), where the test was initially proposed (Greenwald, Nosek, & Banaji, 2003).…”
Section: Suicide-implicit Association Testmentioning
confidence: 99%
“…Consistent with these ideas, existing work has provided evidence that automatic partner attitudes predominantly drive responding when people are less willing or less able to engage in effortful processing-either because of the nature of behavior (e.g., nonverbal communication, Faure et al, 2018), the condition in which it is enacted (e.g., stress, Hicks et al, 2020), or the dispositions pertaining to the actor (e.g., working memory capacity, Murray et al, 2012;self-esteem, Murray et al, 2015; perceived barriers to exit the relationship, Scinta & Gable, 2007). For instance, Hicks and colleagues (2020) demonstrated that although automatic partner attitudes tended to be unrelated to self-reported relationship satisfaction in a meta-analysis and several direct tests, these attitudes were positively associated with deliberate judgments about the relationship when people were financially incentivized to be accurate about their gut feelings toward their partner or if their relationship had dissolved (i.e., reduced motivations) or when they experienced higher stress (i.e., reduced opportunities).…”
Section: Practical Implications For Judgment Behavior and Real-worlmentioning
confidence: 87%
“…Further, what is critical to note is that researchers can directly examine any contextual factors-whether they be cultural or relationship-specific-that do influence automatic partner attitudes. Because relationships have their own contexts that can be measured and tracked over time through videotaped problem-solving interactions (Faure, Righetti, Seibel, & Hofmann, 2018), diary studies (Murray, Gomillion, Holmes, & Harris, 2015), and longitudinal designs (McNulty et al, 2014), researchers can use such methods to directly assess contextual factors (e.g., work, stress, children, cultural beliefs, etc.) and examine the extent to which automatic attitudes change in response to environmental versus relationship experiences.…”
Section: Nature Of Automatic Attitudes: Person-culture Controversiesmentioning
confidence: 99%
See 1 more Smart Citation